Analisis Kualitatif Budaya Organisasi dan Implikasinya terhadap Kinerja Pendidik dalam Perspektif Psikologi Organisasi Positif - Irfieh, Fauzia; Madaniah, Lilim Halimatul; Sanusi, Hary Priatna (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2026)
Efforts to improve educator performance often rely on structural approaches and material incentives, while the dimensions of meaning, values, and subjective experience within the school's organizational culture receive insufficient in-depth attention. This study aims to explore in depth how the construction of organizational culture—specifically values, rituals, narratives, and everyday practices—is understood, experienced, and made meaningful by educators, and how this meaning-making influences their motivation, engagement, and ultimately their performance. This research uses a qualitative phenomenological approach with a multi-site case study design in two senior high schools (one public and one private Islamic school) with distinct cultural characteristics. Data were collected through in-depth interviews with 15 educators and school principals, participatory observation over four months, and document analysis. Data were analyzed thematically using the interactive model by Miles, Huberman, and Saldaña (2014). The research findings reveal three main themes: (1) "Culture as a Co-Constructed System of Meaning," where high performance emerges when core values (such as collaboration and appreciation) are communicated consistently and internalized through social rituals; (2) "The Gap Between Aspiration and Practice: A Fragmented Culture," where inconsistencies between espoused values and enacted values create cognitive dissonance and reduced work engagement; (3) "The Psychology of Interpersonal Space: Leadership as a Catalyst for Psychological Climate." Conclusion: Educator performance is not solely determined by individual factors but is profoundly influenced by the collective psychological climate shaped and maintained by the organizational culture. The effectiveness of culture lies in its ability to create coherence between symbolic meaning and everyday practical experience, which ultimately affects educators' commitment and psychological energy. Recommendations focus on the importance of a meaning-centered leadership approach in school management.